Mechanisms Associated with Acquisition of Resistance to Butyrate-Induced Apoptosis in Colorectal Cancer Cells Using Gene Expression Analysis - YC Fung Kim; Kerr Caroline; Henderson Steven; Priebe Ilka; Shaw Jan; J Buckley Michael; Lockett Trevor; Head Richard; Cosgrove Leah (Journal of Proteomics and Genomics Research, 2014)
Colorectal cancer is one of the most commonly diagnosed cancers worldwide and its prevalence can be reduced by changes to lifestyle and diet. Fermentation of dietary fibre by the gut microbiota and formation of short chain fatty acids, in particular butyrate, is widely thought to play a role in preventing development of the disease. Despite butyrate’s known pro-apoptotic effects, a subpopulation of cancer cells is able to overcome these anti-neoplastic effects of colonic luminal butyrate to proliferate and establish tumours in vivo. In this study, a time course analysis of HT29 and HT29-BR cells treated with butyrate was conducted and global gene expression analysis was used to identify novel mechanisms associated with butyrate-induced apoptosis and in the acquisition of butyrate resistance. Bioinformatic analysis of the data identified deregulated O-GlcNAcylation activity and disruption to gene transcription by BRD4 as possible factors involved with butyrate-induced apoptosis. EGF signalling was identified as being potentially involved in the acquisition of butyrate resistance. Furthermore, the expression of the minichromosome maintenance protein family was significantly reduced in the HT29-BR cell line reflecting disruptions to the DNA replication process. Together, this may confer a unique survival advantage for cells with acquired butyrate resistance.
Keywords: butyrate